PEMBELAJARAN BERBASIS LINGKUNGAN ALAM TERHADAP PEMAHAMAN KONSEP SISWA PADA MATERI SIKLUS AIR - Suci Ariani; Fauzan Fauzan; Fatkhul Arifin (Muallimuna : Jurnal Madrasah Ibtidaiyah, 2022)
This study aims to determine the results and process of increasing students' conceptual understanding of the water cycle material through natural environment-based learning in class V. The method used is classroom action research (CAR) which adapts the Kemmis and Mc. Taggart model which in this study has four components consisting of planning, action, observation and reflection. The instrument used to measure the increase in students' conceptual understanding used a concept understanding test, while the instrument used to measure the improvement in the learning process used observation sheets for teacher and student activities as well as student daily observation sheets and the last one was documentation. The subjects in this study consisted of 16 fifth grade students. The results of this study indicate that there is an increase in conceptual understanding after the implementation of the natural environment-based learning model in the water cycle science subject, which is characterized by an increase in the results of understanding the concept and changes in student behavior after the actions are carried out in each cycle. This can be seen from the increase in the results of the concept understanding test in cycle I and cycle II. In the first cycle, the class average was 86.62 and increased in the second cycle with the class average of 91.12. In addition, the results of this increase are also strengthened by an increase in student behavior, where the results obtained in the first cycle of 65% and an increase in the results in the second cycle to 89%. This shows that the application of natural environment-based learning can be an alternative science learning model, because this learning model can improve the understanding of fifth grade students in the water cycle material